2017
DOI: 10.1002/elps.201700093
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles functionalized with ampicillin

Abstract: The resistance of pathogenic bacteria to antibiotics has become a serious problem. The emphasis is placed on the development of new, effective antimicrobial strategies. One of them is the use of AgNPs in association with antibiotic drugs. The aim of this study was to obtain silver nanoparticles functionalized with ampicillin and to investigate the mechanism of binding antibiotics to nanoparticle using high-performance liquid chromatography approach. To confirm the occurrence of silver nanoparticles functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…When ampicillin was conjugated with plant extracts, 1,383 (C-H bending) and 1,234 (C-O Stretching) were observed with acetone extract, and 2,953 (C-H stretching) and 1,111 (C-O Stretching) were observed with methanol extracts. These functional groups were also observed in the ampicillin FTIR spectra when conjugated to nanoparticles, hence this showed that new bonds were formed when plants extract were conjugated to silver nanoparticles 24 .The adsorption or binding of the antibiotic around the surface of the nanoparticles is indicated by the presence of characteristic bands in FTIR spectra, in penicillin methanol extracts 2,988 and 2,839 (C-H stretching) were observed as new functional group while 2,831 (C-H Stretching), 1,401 (C = C isolated) and 1,009 (C-O Stretching) bands where observed in vancomycin-methanol extracts.…”
Section: Discussionmentioning
confidence: 76%
“…When ampicillin was conjugated with plant extracts, 1,383 (C-H bending) and 1,234 (C-O Stretching) were observed with acetone extract, and 2,953 (C-H stretching) and 1,111 (C-O Stretching) were observed with methanol extracts. These functional groups were also observed in the ampicillin FTIR spectra when conjugated to nanoparticles, hence this showed that new bonds were formed when plants extract were conjugated to silver nanoparticles 24 .The adsorption or binding of the antibiotic around the surface of the nanoparticles is indicated by the presence of characteristic bands in FTIR spectra, in penicillin methanol extracts 2,988 and 2,839 (C-H stretching) were observed as new functional group while 2,831 (C-H Stretching), 1,401 (C = C isolated) and 1,009 (C-O Stretching) bands where observed in vancomycin-methanol extracts.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, the spectrum of the amikacin showed that the bands at 1626 cm −1 corresponding to a carbonyl group and 3400 cm −1 for a primary amine disappeared completely ( Figure 3 b’) after being combined with the nanoparticles. Those results of the FTIR suggest that the functional groups of the antibiotics could be involved in the interaction by hydrogen bonds with gallic acid [ 28 , 29 ]. The results showed in Figure 3 are in concordance with the previous results of the Hua Deng et al, 2016, who carried out UV–Vis and Raman spectroscopy studies reveal that amikacin can form complexes with AgNPs, while ampicillin do not [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…It may also be explained by the possible interactions made with the polymers CA and PCL by means of hydrogen bonding [42]. These peaks were also identified in the ampicillin-modified fibers and were attributed to inplane vibrations of the -CH groups [δCH(ph)] and to the stretching vibration of the -C-C groups, respectively [43]. At 1452 cm −1 , the characteristic peak of the -C-OH absorption bending vibration from the alcohol moieties of the EOs was detected.…”
Section: Chemical Compositionmentioning
confidence: 96%